The Interdisciplinary Approach and It’s Contribution to the Study of Living Hadith : Pendekatan Interdisipliner dan Kontribusinya dalam Studi Living Hadis - Junianto, Viki; Mo’afi; Amrulloh (Jurnal Living Hadis, 2023)
The term "Living Hadith" represents a new variant in Hadith studies. The author will elucidate the interdisciplinary approach that has been employed in Living Hadith studies and its contributions. This research applies literature review methodology. Data is collected from Google Scholar research within the timeframe of 2017-2023. Subsequently, the data is classified and analyzed. This study identifies three interdisciplinary approaches most commonly utilized by Living Hadith researchers: phenomenology, sociology of knowledge, and ethnography. The study also demonstrates the contributions of interdisciplinary approaches in Living Hadith studies, including preventing Living Hadith researchers from falling into subjective judgment and unilateral justifications, as well as avoiding the limitation of Living Hadith studies to the mere description of a tradition subsequently grounded in Hadith. Instead, these approaches make the study more intriguing by drawing diverse conclusions in line with the interdisciplinary approach employed.